Respuesta :

[tex]\huge\underline{\red{A}\blue{n}\pink{s}\purple{w}\orange{e}\green{r} -}[/tex]

the following expression can be solved as follows ~

[tex] \frac{x}{3} + 1 = \frac{x}{8} + \frac{1}{11} \\ [/tex]

Taking LCM on both the sides ,

[tex] \frac{x + 3}{3} = \frac{11x + 8}{88} \\ [/tex]

On cross multiplying ,

[tex]( x + 3)88 = (11x + 8)3 \\ \\ \implies \: 88x + 264 = 33x + 24[/tex]

let's now gather the like terms at either sides of the equation and solve ~

[tex]88x - 33x = 24 - 264 \\ \\ \implies \: 55x = - 240 \\ \\ \implies \: x = \cancel\frac{ - 240}{55} \\ [/tex]

on further simplifying ,

[tex]\implies x = \frac{ - 48 }{ 11} \\ [/tex]

hope helpful ~